2020
DOI: 10.1017/s1754470x20000318
|View full text |Cite
|
Sign up to set email alerts
|

OCD and COVID-19: a new frontier

Abstract: People with obsessive-compulsive disorder (OCD) are likely to be more susceptible to the mental health impact of COVID-19. This paper shares the perspectives of expert clinicians working with OCD considering how to identify OCD in the context of COVID-19, changes in the presentation and importantly what to consider when undertaking Cognitive Behaviour Therapy (CBT) for OCD in the current climate. The expert consensus is although the presentation of OCD and treatment may have become more difficult, CBT should s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 20 publications
1
36
0
1
Order By: Relevance
“…These items in the CY-BOCS questionnaire bear resemblance to public health guidelines during COVID-19 (frequent hand washing and surface cleaning). Thus, we suggest that distinguishing between OCD-related cleaning compulsions and obsessions may be difficult, due to public health instructions regarding avoidance of contamination with COVID-19 ( Jassi et al, 2020 ). The latter could yield over-representation of these symptoms among persons with OCD, as part of a general increase in practicing health protective cleaning habits in the general population, and not necessarily as OCS behavior.…”
Section: Discussionmentioning
confidence: 98%
“…These items in the CY-BOCS questionnaire bear resemblance to public health guidelines during COVID-19 (frequent hand washing and surface cleaning). Thus, we suggest that distinguishing between OCD-related cleaning compulsions and obsessions may be difficult, due to public health instructions regarding avoidance of contamination with COVID-19 ( Jassi et al, 2020 ). The latter could yield over-representation of these symptoms among persons with OCD, as part of a general increase in practicing health protective cleaning habits in the general population, and not necessarily as OCS behavior.…”
Section: Discussionmentioning
confidence: 98%
“…A survey of 2200 Americans, at a time when the number of confirmed COVID-19 cases in the US was 5, with no fatalities, found that 37% of those polled were worried and concerned about the new SARS-CoV-2 virus, and 25% were more concerned in connection with the COVID-19 pandemic than the Ebola outbreak in 2004 [7]. With the exception of the immediate threat of COVID-19, the psychological impact of the pandemic was observed on the mental health of the general population, including tendencies to closely observe the functioning of the body-analysing cough, shortness of breath and constantly monitoring body temperature-and the appearance of mental disorders with a state of anxiety and panic and obsessive-compulsive disorders in connection with justified recommendations for washing and disinfecting hands [146][147][148]. Psychotic exacerbations or even psychosis have been reported among previously mentally unstable people who succumbed to disinformation during the pandemic [149,150].…”
Section: The Covid-19 Pandemic As a Psychological Stress Factormentioning
confidence: 99%
“…Rather than using alternative interventions, adept clinicians should be aware of what usual risk entails and use this to inform patient care. More clearly, ERP should be used during the COVID-19 pandemic, with providers and patients adhering to guidelines set by governmental agencies (i.e., CDC), rather than guidelines determined by a patient’s OCD symptoms [12] . A list of contamination related exposures used by the authors during the pandemic are provided in Table 2 .…”
Section: Exposure and Response Preventionmentioning
confidence: 99%